Unique concurrent appearance of two rare conditions in a young girl: central precocious puberty due to hypothalamic hamartoma and uncommon type of diabetes - Mirjana Kocova; Nikolina Zdraveska; Elena Sukarova-Angelovska (Walter de Gruyter GmbH, 2011)
Hypothalamic hamartomas (HH) are rare congenital nonneoplastic lesions of the tuber cinereum, which usually present as precocious puberty of central origin in young girls and respond well to treatment with long acting gonadotropin releasing hormone (GnRH) analogs. No association of this condition with diabetes mellitus of any form has been reported so far. On the other hand, diabetes mellitus in children and adolescents, when it is not autoimmune type 1 diabetes, is difficult to classify. We present a girl with early onset of central precocious puberty at the age of 8 months, due to hypothalamic hamartoma. Treatment with depot of a GnRH analog for a period of 9 years and 8 months was successful, and her puberty continued 6 months after the discontinuation of triptorelin. At the age of 9 years 6 months, the girl presented with diabetes. She was negative for islet, GAD and IA2 antibodies and her insulinemia and C-peptide remained within normal limits during the 2 years of follow-up. Her metabolic control is excellent with a combination of metformin and a low-dose of mixed insulin. To our knowledge, this is the first description of the simultaneous appearance of these two endocrinological conditions.